The effectiveness recruitment method of employee in the fast food industry - Natrah, Zulkipli (2016)
The well selected and well placed of the employee would not be only contribute to the efficient running of the organization but offer significant potential for the future replacement. These hiring is an important function. The process of hiring will begins with human resources planning (HRP) which have responsibility to determine the type and number of people on organization needs. The scope of this study is focusing on the effectiveness recruitment method of employee in fast food industry. The most important recruitment method will be ranking. Besides, that, in this research the challenges recruitment of employee in fast food industry will also be examined. A questionnaire survey was conducted to find out the effectiveness recruitment method of employee and challenges recruitment of employee. The field survey conducted included Human Resources staff for every branch of fast food. About 52 respondents had participant in this research.